OsZIP4, a novel zinc-regulated zinc transporter in rice - Ishimaru, Yasuhiro (Journal of experimental botany, 2005)
Zinc (Zn) is an essential element for the normal growth of plants but information is scarce on the mechanisms whereby Zn is transported in rice (Oryza sativa L.) plants. Four distinct genes, OsZIP4, OsZIP5, OsZIP6, and OsZIP7 that exhibit sequence similarity to the rice ferrous ion transporter, OsIRT1, were isolated. Microarray and northern blot analysis revealed that OsZIP4 was highly expressed under conditions of Zn deficiency in roots and shoots. Real-time-PCR revealed that the OsZIP4 transcripts were more abundant than those of OsZIP1 or OsZIP3 in Zn-deficient roots and shoots. OsZIP4 complemented a Zn-uptake-deficient yeast (Saccharomyces cerevisiae) mutant, Deltazrt1,Deltazrt2, indicating that OsZIP4 is a functional transporter of Zn. OsZIP4-synthetic green fluorescent protein (sGFP) fusion protein was transiently expressed in onion epidermal cells localized to the plasma membrane. In situ hybridization analysis revealed that OsZIP4 in Zn-deficient rice was expressed in shoots and roots, especially in phloem cells. Furthermore, OsZIP4 transcripts were detected in the meristem of Zn-deficient roots and shoots. These results suggested that OsZIP4 is a Zn transporter that may be responsible for the translocation of Zn within rice plants